IMPLEMENTASI PEMBELAJARAN BERBASIS PROYEK KELAS IV DI SD NEGERI 2 KAMPUNG BARU BANDAR LAMPUNG - Qomario Qomario; Ali Mashari (Universitas Negeri Medan, 2019)
Curriculum 2013 in elementary schools was implemented with thematic learning, but the teacher for fourth grade in SD Negeri 2 Kampung Baru had not yet maximized learning with a scientific approach. The aim of this research was to analyze the effect of the implementation of project-based learning on the thematic learning outcomes of grade IV SD Negeri 2 Kampung Baru Bandar Lampung. This research used a quasi-pretest-posttest design experimental group. The population of the students was 65 students, the sample was determined by random sampling techniques amounted to 25 students. The data was collected by multiple choice tests with total 20 questions. Based on the test, the data was obtained by t = 12.849 (consulted with table t) db = N-1 = 25 -1 = 24 with ttable (α = 0.05) = 1.711, because thit ≥ ttabel or 12.849 is bigger than 1,711, there is an influence after doing the project based learning (PjBL). There is a significant difference between the results of the pretest and posttest learned through the project based learning model. The posttest average was 82% higher than the pretest average of 59%. This shows that there is a percentage of enhancement 23%.Keywords: Project Based Learning, Thematic Learning, Scientific Approach, Elemantary School